The cortical neuroanatomy of neuropsychological deficits in mild cognitive impairment and Alzheimer's disease: A surface-based morphometric analysis - Ahn, Hyun-Jung; Seo, Sang Won; Chin, Juhee; Suh, Mee Kyung; Lee, Byung Hwa; Kim, Sung Tae; Im, Kiho; Lee, Jong-Min; Lee, Jun Hong; Heilman, Kenneth M.; Na, Duk L. (Neuropsychologia, 2011)
► There are different patterns of cortical thinning associated with neuropsychological tests. ► The neuropsychological tests have a hemispheric laterality associated with each functions. ► The patterns of cortical thinning are pathological markers for cognitive dysfunction. Patients with probable Alzheimer's disease (AD) and the amnesic form of mild cognitive impairment (aMCI) often demonstrate several types of neuropsychological deficits. These deficits are often related to cortical atrophy, induced by neuronal degradation. The purpose of this study is to investigate whether different anatomic patterns of cortical atrophy are associated with specific neuropsychological deficits. The participants were 170 patients with AD and 99 patients with aMCI. All participants underwent the Seoul Neuropsychological Screening Battery (SNSB), which includes tests that assess attention, language, visuospatial functions, verbal and visual memory, and frontal/executive functions. Cortical atrophy (thinning) was quantified by measuring the thickness of the cortical mantle across the entire brain using automated, three-dimensional magnetic resonance imaging. The relationship between cortical thickness and neuropsychological performance was analysed using stepwise multiple linear regression analyses. These analyses (corrected P<.001) showed that several specific brain regions with cortical thinning were associated with cognitive dysfunction including: digit span backward, verbal and picture recall, naming and fluency, drawing–copying, response inhibition and selective attention. Some of the other functions, however, were not associated with specific foci of cortical atrophy (digit span forward, the word reading portion of the Stroop test, word and picture recognition). Our study, involving a large sample of participants with aMCI and AD, provides support for the postulate that cortical thinning-atrophy in specific anatomic loci are pathological markers for specific forms of cognitive dysfunction.